Enhanced node cooperation technique for outwitting selfish nodes in an ad hoc network. Issue 2 (1st March 2015) - Kaushik, Rekha; Singhai, Jyoti
Abstract : In an ad hoc network, selfish nodes do not cooperate in packet forwarding of other nodes to maximise their own welfare. Such nodes will have a negative effect on the performance of the network. In this study, an enhanced node cooperation technique (ENCT) is proposed which is a hybrid technique of reputation‐based mechanism and incentive‐based mechanism. It evaluates relaying nodes' behaviour, calculates its reputation and outwitting selfish nodes by utilising receipts submitted by each relaying node in the path to a centralised authority rather than using promiscuous mode. A mathematical analysis is provided which demonstrates that the expected gain of reputation for a particular node is maximum if it adopts cooperative behaviour. To motivate nodes for cooperation, variable incentives are provided proportionate to their reputation and current behaviour. Simulation results demonstrate modification of reputation and incentive with varying number of selfish nodes, traffic connections, and topology with static and dynamic behaviour of selfish nodes. The result shows that the ENCT is robust, fair and efficient technique.